Development of the Design and Control of a Hexapod Robot for Uneven Terrain - Putra, Prasetya Murdaka; Widodo, Nuryono Satya (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
In the Indonesian Search and Rescue Robot Contest in 2021 and 2022, the robot still cannot work well when passing through uneven obstacles. The change in uneven terrain from the previous year was a difficulty for the robot in passing it. This research was conducted to develop mechanical design and movement control design for the robot, so that the robot can be more optimal when moving through uneven terrain. The design of the hexapod robot is done by reducing the dimensions of the existing robot and determining the Center of Gravity point. The movement of the robot is also designed by determining the angular position of the AX-18A servo with respect to the terrain the robot travels through. The movement algorithm applied to the robot is the tripod gait algorithm. The robot control on the debris field and irregular floor is done by applying a proximity sensor to minimise the robot from hitting the wall on the field. The robot also has an IMU sensor that will work in measuring the slope on the up-and-down floor terrain (slope), so that the movement of the robot can be adjusted when passing through the terrain with the slope read by the sensor. The results of the research conducted show that the robot can be redesigned through 3D design through solidworks by determining the Center of Gravity (CoG) point. The robot has been able to pass through 3 objects tested, namely debris terrain, irregular floor terrain, and up and down floor terrain. The success rate of the robot when passing through debris terrain and irregular floor terrain is 100% with an average time of 9.7 seconds and 10.1 seconds. The success rate of the robot when passing through the up-and-down floor terrain is 80% with an average time of 22.9 seconds.